PERAN INOVASI TEKNOLOGI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI ERA DIGITAL - Asriani Juneva; Jorgi Jorgi; Julita Julita; Devi Dawa; Mirna Mirna (JIP: Jurnal Ilmu Pendidikan, 2025)
Education in the digital era is experiencing significant transformation along with technological developments. Innovations in educational technology, such as digital-based learning, artificial intelligence, and e-learning platforms, provide great opportunities to improve the quality of learning. This article discusses the role of technological innovation in creating more interactive, collaborative and personalized learning methods according to student needs. Apart from that, challenges in implementing technology, such as the digital divide and the readiness of teaching staff, are also a major concern. With the right approach, the use of technology can increase learning motivation, strengthen 21st century skills, and support a more flexible and adaptive learning system. This study highlights the importance of synergy between teachers, students and educational policies in optimizing the use of technology for more effective and inclusive learning.